Preparation and Evaluation of Sustained Release Tablets of Nifedipine Solid Dispersions - ابراهيم, وهاد; هارون, محمد; صقر, رنيم (Latakia University Journal -Medical Sciences Series, 2020)
Nifedipine is one of the most used calcium channel blocking agents. Due to its low aqueous solubility, it often shows low and irregular bioavailability after oral administration. Nifedipine has short half-life so it has to be administered many times a day. Immediate-release formulations increase the risk of myocardial infarction and mortality. This research aims to prepare dual-function drug delivery system to enhance nifedipine solubility using solid dispersion technique, and extend its release by incorporating these dispersions in matrix tablets. 32 Factorial design was employed; two independent variables, Poloxamer 188 and Ethyl cellulose, to improve solubility and extend release respectively, were used in 3 levels. The prepared tablets were examined, and succeeded in extending nifedipine release up to 12 hrs. The equations that link the dependent and independent variables were obtained, through which tablet hardness and the released amount after 1, 4 and 6 hours could be predicted.